Hygienic and sanitary conditions of eggs marketed in different cities in Brazil: a review (Research, Society and Development, 2021)
In the context of the food crisis that Brazil has been suffering in the year 2021, increasingly aggravated by the extension of the current pandemic situation, more and more families have replaced foodstuffs in their diet. Meats, which had already been suffering high prices over the past few years, are replaced by other types of protein sources, especially eggs. Eggs are food widely traded in Brazil and widely consumed by the population in general. They are a highly nutritious food that can be consumed with great versatility. However, eggs when not handled and packaged properly, can pose risks to the consumer's health. Microorganisms such as Salmonella sp., Staphylococcus aureus and coliforms are largely responsible for outbreaks of infections and gastrointestinal poisoning. This study brings a survey of the main articles published in the last 6 years, on the hygienic and sanitary conditions of eggs sold in different regions of Brazil. The articles were obtained from research through sites such as SciELO and Google Scholar. As a result of the research, 14 articles were selected, between the years 2015 to 2020, which studied the topic in different cities in Brazil. It is possible to notice that the quality of the commercialized eggs is very diverse and the studies vary a lot between different cities in Brazil. Many articles do not address microbiological studies, which would be extremely important to determine the quality of the eggs analyzed.